Low Packet Latency Using New Radio Duty-Cycle Scheduling Method - Setyawati, Onny; Muhammad, Abdur R.; Basuki, Achmad (Journal of Information Technology and Computer Science, 2023)
As energy conservation in Wireless Sensor Networks is crucial, the scheduling methods are required to ensure that sensor nodes operate for a longer period. Duty cycle scheduling can be accomplished using synchronous, asynchronous, or on-demand methods with additional radio channels. This study has integrated the on-demand method with an asynchronous scheduling mechanism for the wake-up radio. Model simulation results with random placements showed that the Wake-up Asynchronous On-demand Radio Duty-Cycle (WAORDC) method was able to achieve the latency value of 3.3 seconds, better than the CXMAC asynchronous method, and the total energy required was approximately 4% only, to activate the sensor node.